Integrated engineering education through design activities: A signal phase module design case study for traffic engineering course - Zhu, Sicong; Yuan, Yufei; Peng, Wenjie; Wu, Hangbin; Yu, Lei; Lan, Qing (Computer applications in engineering education, 2024)
This article presents an integrated educational module for undergraduate traffic engineering at the microscale level. When dealing with a complex transportation system, the education program should cultivate students’ acquisition of both in‐depth traffic specialization and breadth of engineering knowledge. For the educational instruction of the signal phase design, this article presents an integrated design that includes several engineering subjects: signal phase design, circuits and electronics, and object‐oriented programming (OOP). Due to the lengthy evolution of signal phase design and the high‐end industrial standards for this issue, this well‐structured problem requires an instructional design to adopt a worked example that integrates varied engineering domains. The integrated design session is intended to deliver education through designing a miniature signal controller while creating an immersive situation and encouraging social teamwork. Feedback from participating students has been positive, indicating the achievement of the planned learning objectives and better mastery of engineering practices.